Efforts to Increase Public Awareness of Sumberjaya Village, Cihaurbeuti District, Regency Ciamis Related to Regulations Limiting Community Activities - Setyawan, Muhamad Fauzi; Ratnawaty, Latifah (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Enforcement of Restrictions on Community Activities (PPKM). This PPKM is carried out to limit interactions, and meetings between people and people and groups with groups, which is expected to reduce the transmission of COVID-19- 19The problems raised in this scientific article are about. 1. What did the residents of Sumberjaya Village, Ciamis Regency do during PPKM. And 2. How did the residents of Sumberjaya village respond to the Covid-19 vaccine, for the method used in this study using interviews. The results of the research that have been obtained when PPKM is that the residents of Sumberjaya village strictly obey the regulations that have been issued by the government, and the response of the Sumberjaya Village residents to the vaccine is very good and many residents are also hunting for vaccines for the sake of immunity. The conclusion obtained in this study is that PPKM and vaccines have a lot of advantages and disadvantages, the disadvantages of PPKM are the reduction in the household economy and the advantage of vaccines is to increase immunity.